1995
DOI: 10.1093/rheumatology/34.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Disease Phenotype in Monozygotic Twins Concordant for Rheumatoid Arthritis

Abstract: The objective of the study was to investigate the genetic contribution to the clinical expression of rheumatoid arthritis (RA) by comparison of disease features in RA-concordant monozygotic (MZ) twin pairs. Fourteen RA-concordant MZ twin pairs recruited from a nation-wide study were examined to determine the degree of similarity in: (a) age of disease onset; (b) pattern of joint involvement; (c) pattern of extra-articular disease; (d) toxic reactions to drugs; (e) disease course; and (f) serology for rheumatoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Multiple studies observed both total Ig and antigen-specific titers to be more correlated in monozygotic twins than dizygotic twins or unrelated individuals (16)(17)(18). In some cases of monozygotic twins discordant for autoimmune diseases, the healthy twin often shared high autoantibody reactive titers with their affected twin (16,19,20).Early sequencing studies were able to identify some systematic biases in the antibody repertoire with limited sampling depth. The first sequencing studies to characterize V(D)J diversification mechanisms identified the gene segment recombination process, but also implied a repertoire too diverse to exhaustively interrogate by traditional sequencing technologies (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies observed both total Ig and antigen-specific titers to be more correlated in monozygotic twins than dizygotic twins or unrelated individuals (16)(17)(18). In some cases of monozygotic twins discordant for autoimmune diseases, the healthy twin often shared high autoantibody reactive titers with their affected twin (16,19,20).Early sequencing studies were able to identify some systematic biases in the antibody repertoire with limited sampling depth. The first sequencing studies to characterize V(D)J diversification mechanisms identified the gene segment recombination process, but also implied a repertoire too diverse to exhaustively interrogate by traditional sequencing technologies (21).…”
mentioning
confidence: 99%
“…Multiple studies observed both total Ig and antigen-specific titers to be more correlated in monozygotic twins than dizygotic twins or unrelated individuals (16)(17)(18). In some cases of monozygotic twins discordant for autoimmune diseases, the healthy twin often shared high autoantibody reactive titers with their affected twin (16,19,20).…”
mentioning
confidence: 99%
“…Nonetheless, MZ twins concordant for RA manifest consistent within-pair diversity in different variables, i.e. pattern of joint involvement, occurrence of extra-articular disease and adverse drug reactions, while some similarity was found for age at disease onset, bone erosions, and serum rheumatoid factor (RF) [32]. In the case of RF, the expression of the variable region determinants in RF are generally similar within MZ twins, but different between unrelated twin pairs irrespective of the disease status [33], while RF isotypes may be influenced by genetic factors.…”
Section: Mechanismsmentioning
confidence: 99%
“…Genetic variation in the human leukocyte antigen region is a contributing factor to the genetic risk of RA 40 . The disease also exhibits a higher concordance rate in identical twins than in fraternal twins 41 .…”
mentioning
confidence: 99%